A Genome-Wide Association Study for Tolerance to Paratuberculosis Identifies Candidate Genes Involved in DNA Packaging, DNA Damage Repair, Innate Immunity, and Pathogen Persistence - Canive, María; Badia-Bringué, Gerard; Vázquez, Patricia; Garrido, Joseba M.; Juste, Ramón A.; Fernandez, Almudena; González-Recio, Oscar; Alonso-Hearn, Marta (Frontiers in Immunology, 2022)
Although the genetic susceptibility to diseases has been extensively studied, the genetic loci and the primary molecular and cellular mechanisms that control disease tolerance are still largely unknown. Bovine paratuberculosis (PTB) is an enteritis caused by Mycobacterium avium subsp. paratuberculosis (MAP). PTB affects cattle worldwide and represents a major issue in animal health. In this study, the associations between host genetic and PTB tolerance were investigated using the genotypes from 277 Spanish Holstein cows with two distinct phenotypes: cases) infected animals with positive PCR and bacteriological culture results but without lesions in gut tissues (N= 24), and controls) animals with negative PCR and culture results but with PTB-associated lesions (N= 253). DNA from peripheral blood of the study population was genotyped with the Bovine EuroG MD Bead Chip, and the corresponding genotypes were imputed to whole-genome sequencing (WGS) data. A genome-wide association study was performed using the WGS data and the defined phenotypes in a case-control approach. A total of 142 single nucleotide polymorphisms (SNPs) were associated (false discovery rate ≤ 0.05, P values between 1.5 × 10-7 and 5.7 × 10-7) with tolerance (heritability= 0.55). The 40 SNPs with P-values < 5 × 10-7 defined 9 QTLs and 98 candidate genes located on BTA4, BTA9, BTA16, BTA25, and BTA26. Some of the QTLs identified in this study overlap with QTLs previously associated with PTB, bovine tuberculosis, mastitis, somatic cell score, bovine diarrhea virus persistent infection, tick resistance, and length of productive life. Two candidate genes with important roles in DNA damage response (ERCC4 and RMI2) were identified on BTA25. Functional analysis using the 98 candidate genes revealed a significant enrichment of the DNA packaging process (TNP2/PRMI1/PRM2/PRM3). In addition, the TNF-signaling (bta04668; TRAF5/CREB5/CASP7/CHUK) and the toxoplasmosis (bta05145; TGFβ2/CHUK/CIITA/SOCS1) pathways were significantly enriched. Interestingly, the nuclear Factor NF-κβ Inhibitor Kinase Alpha (CHUK), a key molecule in the regulation of the NF-κB pathway, was enriched in both pathways. Taken together, our results define a distinct immunogenetic profile in the PTB-tolerant animals designed to control bacterial growth, modulate inflammation, limit tissue damage, and increase repair, thus reducing the severity of the disease.